SHAPING SPIRITUALITY THROUGH CHILDREN’S LITERATURE INTENDED FOR PRIMARY SCHOOL – DISCUSSION OF SELECTED EXAMPLES - Baracz, Weronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim is to learn about the spirituality like a part of education. Spirituality is understood as values, attitudes and traditions choosing by man. It also refers to the integral, holistic upbringing of the human being. In this article, attention is paid to the comprehensive, multidimensional pupil development. This objective will be achieved by analyzing selected children's books. Short outline of the research problem and novelty.